Modern aspects of mass spectrometry: proceedings - NATO Advanced Study Institute of Mass Spectrometry on Theory, Design, and Applications (1966: Glasgow, Scotland); Reed, Rowland I.; North Atlantic Treaty Organization. Advanced Study Institute (New York : Plenum Press, 1968)
40